Reconstructing the Authority of Village Heads in a Democratic Local Government System: Rekonstruksi Kewenangan Lurah dalam Sistem Pemerintahan Daerah yang Demokratis - Susanti, Indira Tanty; Sesung, Rusdianto (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The authority of the Lurah (urban village head) plays a pivotal role in Indonesia’s regional governance, yet it is often hindered by overlapping regulations and the complexities of regional autonomy. Specific Background: Regulatory evolution and decentralization have created inconsistencies in defining the Lurah’s scope of power. Knowledge Gap: Limited scholarly work has addressed the disharmony between attributive, delegative, and mandate-based authorities in the context of democratic governance and Administrative Law. Aim: This study seeks to reconstruct the Lurah’s authority to ensure greater alignment with democratic principles and the General Principles of Good Governance (AUPB). Results: Through a normative juridical method, combining statutory and conceptual approaches with case studies in major Indonesian cities, the findings reveal significant regulatory disharmony and insufficient AUPB integration. Novelty: The research proposes a participatory, responsive, and legally coherent framework for defining the Lurah’s authority, emphasizing clarity, accountability, and democratic legitimacy. Implications: Strengthening the Lurah’s authority within a transparent and participatory legal structure is essential for enhancing the effectiveness and legitimacy of local governance in Indonesia. Highlights: Clarifies Lurah’s authority to avoid overlap. Aligns governance with AUPB and democracy. Proposes participatory and accountable framework. Keywords: Lurah Authority, Regional Governance, Administrative Law, Good Governance, Democratic Principles